Pengaruh Cekaman Salinitas Terhadap Viabilitas dan Vigor Benih Dua Varietas Kedelai (Glycine max. L.) - MEKSY DIANAWATI; DWI PANGESTI HANDAYANI; YULIANUS R. MATANA; SIMAO MARGONO BELO (Fakultas Pertanian Universitas Udayana, 2013)
The Salinity Stress Effect on Seed Viability and Vigor of Two Varieties of Soybean. Poorseed germination and crop stand are major problems in saline areas. The purpose of this study was todetermine the effect of salinity stress degrees of two varieties of soybeans. This research was conductedin March to April 2011 at the Seed Technology Laboratory, Bogor Agricultural University. Randomizedcompleted design was used with two treatment factors and three replications. First factor was varieties,i.e. Burangrang and Tanggamus. Second factor was consentrations of NaCl, i.e. 0, 2, 4, 6, 8, 10 g l-1.The results showed that the higher consentration of NaCl, the lower germination rate and seedling vigorindex. The NaCl concentration critical point of salinity stress based on germination rate of Burangrangand Tanggamus variety was 6 g l-1.